A high gain antenna utilizing Mu-near-zero metasurface structures for 5G applications. Issue 2 (22nd March 2023) - Abdelaziem, Islam H.; Ibrahim, Ahmed A.; Abdalla, Mahmoud A.
Abstract: A high gain antenna with Mu-near-zero metasurface (MNZ-MS) is introduced in this work. The proposed antenna can be utilized for future 5G applications. The patch antenna is designed on the upper face of the square substrate with a ground plane at the bottom face. To improve the antenna gain, a layer of MNZ-MS unit cells is placed above the antenna substrate with 0.48 λ 0 air space between the two layers, where λ 0 is the wavelength in free space at the resonance frequency of 26.3 GHz. The MNZ-MS layer consists of four double-sided split square resonators. The overall thickness of the proposed antenna is 0.66 λ 0 . To approve the execution of the proposed antenna, a prototype model is manufactured and tested. The outcomes fulfill a reflection coefficient lower than −10 dB over the frequency spectrum of 26–28 GHz. A gain improvement better than 5 dB is obtained compared to the gain of the reference patch at the center frequency of 26.3 GHz.